SNPs in miRNAs and Target Sequences: Role in Cancer and Diabetes - Chhichholiya, Yogita; Suryan, Aman Kumar; Suman, Prabhat; Munshi, Anjana; Singh, Sandeep (Frontiers in Genetics, 2021)
miRNAs are fascinating molecular players for gene regulation as individual miRNA can control multiple targets and a single target can be regulated by multiple miRNAs. Loss of miRNA regulated gene expression is often reported to be implicated in various human disease like diabetes, cancer etc. Recently geneticists across the world started reporting single nucleotide polymorphism (SNPs) in seed sequences of miRNAs. Similarly, SNPs are also reported in various target sequences of these miRNAs. Both the scenarios lead to dysregulated gene expression which may result in progression of disease. In the present paper, we explore SNPs in various miRNAs and their target sequences reported in various human cancers as well as diabetes. Similarly, we also present evidence of these mutations in various other human diseases.